INTEGRATION OF ERROR CORRECTION MODEL IN TESTING THE INTERACTION EFFECT OF CREDIT GROWTH AND BANKING RISK MANAGEMENT IN INDONESIA - Wahyuni, Adinda; Giriati, Giriati; Wendy, Wendy; Mustaruddin, Mustaruddin; Mustika, Uray Ndaru (LPPM STIE Muhammadiah Bandung, 2025)
This study explores the impact of market risk, operational risk, liquidity risk, and solvency risk, while also investigating the moderating effect of credit growth on bank performance. The Error Correction Model-Eagle Granger (ECM-EG) methodology was applied to data from 2014 to 2023. Findings indicate that, in the short term, market and operational risks significantly impact bank performance. In the long term, only solvency risk does not significantly affect bank performance. Additionally, credit growth moderates the relationship between market and liquidity risks and bank performance in the short term, while in the long term, it only moderates the relationship between market risk and bank performance. Our empirical findings demonstrate that effective risk management enhances bank performance. This research provides valuable insights for policymakers, researchers, and academics in fostering a conducive environment for corporate activities.